Man and Nature in Contemporary Ecotopic and Apocalyptic Fiction - Borovec, Jakub (Univerzita Pardubice, 2021)
This bachelor thesis deals with establishing the ecotopian genre with help of the scientific literature from the field of ecocriticism. The theoretical part includes the definition of the ecotopian genre together with its features. The practical part is divided into two chapters. It focuses on the analysis of ecotopian novels - Atwood, Hoyle, Ballard. The aim of this analysis is to include novels into the ecotopian genre and define the relationship between man and nature.
Člověk a příroda v současné ekotopické a apokalyptické próze
Keywords: antropocentrismus; biocentrismus; ekocentrismus; ekokritika; člověk a příroda; anthropocentrism; biocentrism; ecocentrism; ecocriticism; man and nature